PENGARUH STRATEGI BRAND EXTENSION TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE ACER DENGAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING (Studi Pada Pengunjung WTC dan Marina Plaza di Surabaya) - RISANG TEGAR PAMBANGUN, DIMAS (Jurnal Ilmu Manajemen (JIM), 2016)
This study aims to examine and analyze the influence of Brand Extension on Purchase Decision through Brand Image (study on visitor in the Plaza Marina and WTC Mall Surabaya).This type of research is a conclusive research studies. The study is quantitatively analyzed using probability sampling technique by using SEM analysis method. This study used a sample of 200 respondents. The results showed that there are significant direct effect brand extension on brand image and brand image on purchase decision. But, there is no a significant direct effect brand extension on purchase decision. Keywords: Brand Extension, Purchase Decision, Brand Image